The Effect of the Arbitration Agreement on the Parties of the Guarantee Letter in Jordanian Law: Comparative Analytical Study - Zahidh, Jumana Yahia Saleh (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: The study aims to clarify the extent to which the arbitration agreement may be invoked against the parties concerned in contracts related to the letter of guarantee. The latter’s effects are not limited to both parties to the relationship but rather extend beyond it, resulting in a set of rights for third parties who are not a party to the agreement; this is considered a departure from general principles. Methods: The comparative analytical approach was followed to the various legislations that dealt with the subject of the arbitration agreement in the letter of guarantee at the national and international levels, while explaining the position of the Jordanian legislator on the matter. Results: It is necessary to recognize the breadth of the scope of the arbitration contract in the case of a contractual group, given the multiplicity of parties and the existence of a single economic goal. Out of respect for the idea of economic unity, we should not stop at the idea of an explicit signature on the arbitration agreement. Conclusion: The commercial legislator must intervene to regulate the provisions of the guarantee letter, as it is a contract of a special nature that raises many legal problems. By the intervention of the legislator to adopt the criterion of knowledge in extending the arbitration agreement to non-signatories within the framework of the contractual group, it would achieve the idea of economic unity and serve the interests of trade.